Parent Involvement in Schooling Processes: A Case Study in Aceh - Wulandary, Dwi; Herlisa, Herlisa (Yayasan Sukma Bangsa, 2018)
The study focuses on exploring the parents’ understanding of their involvement in schooling processes based on the six typologies of Epstein. The categories of the study were based on the typologies of Epstein consisting of parenting, communicating, volunteering, learning at home, decision-making, and collaboration with the community. Parent involvement in an Aceh school is a crucial issue which needs to be studied. This research provides an analysis of parents’ understanding of their involvement in schooling processes, what different kinds of ways parents/homes and school communicate between each other, and whose parents are frequently involved in schooling. There are several barriers parent involvement in schooling, such as work demands, reluctance to attend the school, lack of communication with the school, and parents’ perception of their involvement. The reason behind parent involvement in schooling processes can be explained with attribution theory. The findings indicated that parent involvement in schooling processes in Aceh is low. In addition, the motivation of parents to be involved in schooling processes was related to their own motives, such as merely to fulfill their obligation as a parent in rearing the children.[Tujuan penelitian ini adalah untuk mengeksplorasi pemahaman orang tua tentang keterlibatan mereka dalam proses pendidikan berdasarkan enam tipologi Epstein. Kategori penelitian ini berdasarkan tipologi Epstein terdiri dari pola asuh, komunikasi, relawan, pembelajaran di rumah, pengambilan keputusan, dan kolaborasi dengan masyarakat. Keterlibatan orang tua di Aceh merupakan isu penting yang perlu diperhatikan. Penelitian ini memberikan analisis tentang pemahaman orang tua tentang keterlibatan mereka dalam proses pendidikan, bagaimana cara orang tua dan sekolah berkomunikasi satu sama lain, dan apakah ayah atau ibu yang dominan terlibat dalam pendidikan anak mereka. Ada beberapa hambatan keterlibatan orang tua di sekolah, seperti tuntutan kerja, keengganan untuk bersekolah, kurang komunikasi dengan sekolah, dan persepsi orang tua terhadap keterlibatan mereka dalam proses pendidikan. Alasan di balik keterlibatan orang tua dalam proses pendidikan dapat dijelaskan dengan teori atribusi. Penelitian ini menemukan bahwa keterlibatan orang tua dalam proses pendidikan di Aceh rendah. Selain itu, motivasi orang tua untuk terlibat dalam proses pendidikan itu terkait dengan motivasi mereka sendiri, seperti semata-mata memenuhi kewajibannya sebagai orang tua dalam membesarkan anak.]